2014
DOI: 10.1186/2047-783x-19-23
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pleural effusion IL-17 is a diagnostic marker and outcome predictor in lung cancer patients

Abstract: BackgroundInterleukin 17 (IL-17) is a proinflammatory cytokine produced mainly by CD4+ T-lymphocytes and may be important in tumor cell growth and progression. In this study, we aimed to evaluate the diagnostic and prognostic value of pleural effusion levels of IL-17 in lung cancer patients with malignant pleural effusion (MPE).MethodsPleural effusion samples were collected from 78 lung cancer patients with MPE and from 45 patients with nonmalignant pleural effusion. Pleural fluid concentrations of IL-17 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…27 Another study found a correlation between high IL-17 protein levels in ovarian carcinoma ascites and improved survival. 69 Finally, a study in gastric cancer patients showed a significant correlation between high IL-17 RNA expression measured by qRT-PCR and improved survival in patients treated with curative resection.…”
Section: A High Number Of Th17 Cells In Tumor-associated Fluids Is Comentioning
confidence: 98%
See 1 more Smart Citation
“…27 Another study found a correlation between high IL-17 protein levels in ovarian carcinoma ascites and improved survival. 69 Finally, a study in gastric cancer patients showed a significant correlation between high IL-17 RNA expression measured by qRT-PCR and improved survival in patients treated with curative resection.…”
Section: A High Number Of Th17 Cells In Tumor-associated Fluids Is Comentioning
confidence: 98%
“…Potential risks of bias identified in categorizing IL-17 or Th17 expression were optimal cut-off values chosen arbitrarily 15,16 or using a minimum p value, 17-23 receiver operating characteristic (ROC) curve [24][25][26][27] or regression tree analysis. 28 Furthermore, one study compared the six long (>3 y) vs. short (<1.5 y) surviving patients.…”
Section: Study Design and Selection Criteriamentioning
confidence: 99%
“…In this regard, IL-17, secreted by CD4+ T cells, has been reported to promote tumor progression by anti-apoptotic and pro-angiogenic mechanisms [5, 6]. IL-17 expression is elevated in various kinds of human tumors such as cervical cancer, hepatocellular carcinoma, ovarian cancer, esophageal cancer, breast cancer, gastric cancer, and NPC [7-10]. IL-17 was proposed to exert significant effects on tumor initiation and progression by affecting the antitumor immune response, [11, 12] and thus a novel immune-evasion mechanism utilized by the tumors through the inhibition of T-helper 17 (Th17) cell development was proposed [13].…”
Section: Introductionmentioning
confidence: 99%
“…Differentiating malignant from benign pleural effusions is a critical clinical problem, and conventional methods have proven inadequate (Xu et al, 2014c). Pleural fluid cytology has traditionally been the analytical method of choice for the detection of tumor cells in pleural fluid.…”
Section: Discussionmentioning
confidence: 99%